Validation of a breath-holding test as a screening test for exercise-induced hypoxemia in chronic respiratory diseases. (23rd April 2021) - Ideguchi, Hideharu; Ichiyasu, Hidenori; Fukushima, Kazuaki; Okabayashi, Hiroko; Akaike, Kimitaka; Hamada, Shohei; Nakamura, Kazuyoshi; Hirosako, Susumu; Kohrogi, Hirotsugu; Sakagami, Takuro; Fujii, Kazuhiko
The detection of exercise-induced hypoxemia is important for evaluating disease status in patients with chronic respiratory diseases. The 6-min walk test (6MWT) is useful for detecting exercise-induced hypoxemia. This pilot study aimed to validate the breath-holding test (BHT) as a screening for exercise-induced hypoxemia and compare its utility with that of the 6MWT in patients with chronic respiratory diseases. Fifty-nine patients with chronic respiratory diseases underwent BHTs lasting 10, 15, and 20 s. Percutaneous oxygen saturation (SpO2 ), pulse rate, and severity of dyspnoea were measured. The participants also underwent a 6MWT, a pulmonary function test, and analysis of arterial blood gas at rest. Multivariate linear regression analysis was performed to identify significant predictors of desaturation in the 6MWT. The minimum SpO2 during the BHT (all durations) and 6MWT were significantly correlated. Receiver operating characteristic analysis revealed the optimal cut-off for predicting SpO2 < 90% during the 6MWT as a minimum SpO2 ≤ 94% during the 15-s BHT. Perceived dyspnoea and maximum pulse rate were significantly lower during the 15-s BHT than during the 6MWT. In the multivariate linear regression analysis, the minimum SpO2 during the 15-s BHT (β, 0.565, p < 0.001) and %DLco (β, 0.255, p < 0.028) were independent predictors of desaturation in the 6MWT. The minimum SpO2 during the 15-s BHT may be a useful measure for screening for exercise-induced hypoxemia in patients with chronic respiratory diseases. The BHT is easier to perform, more readily available, and better tolerated than the 6MWT.